Evaluation of quality of crushed-limestone and -siltstone for road aggregates - Khanal, Shrawan; Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2009)
Aggregates are important constituents of pavement structures. Performance of aggregate layers depends on particle shape, grading and composition and their physical, mechanical and chemical properties. Careful study of these properties allows evaluation of aggregates according to the international norms. There are huge rock outcrops surrounding the Kathmandu Valley. With growing construction in and around the Kathmandu Valley, demand of aggregates has become so high that limited quarry sites within the valley are not sufficient to meet the requirements. Therefore, search of rock outcrops from which suitable aggregates may be quarried is sought to meet the current and future demands of aggregates suitable not only for the building and infrastructures but also for the roads or transport networks in the country. This study aims in exploring and evaluating suitability of natural crushedrock aggregates in western Kathmandu, Nepal for unbound pavement structures. Mainly three kinds of rocks were identified from the outcrops of the study area; siliceous limestone, crystalline limestone and calcareous siltstone. Shape factor (F) ranges from 0.99 to 1.40 in most of the samples indicating their cubic to disc shape. Aggregates have high roughness indices and moderate roundness indices. Flakiness indices of the test samples vary from 14% to 25% and elongation indices from 75.49 to 90.79% indicating that the crushed samples yield very little flat and elongated particles, and huge equant particles, which is very desirable for aggregates. Dry density of samples ranges from 2495 to 2658 kg/m3. WAV varies from 0.20 to 0.67%. ACV ranges from 22-26% and aggregates are strong enough to resist against compressive load. LAA varies from 27 to 30 % and AIV ranges from 10 to 14% showing that the aggregates have good hardness. The average CBR value is 61.12%. SSV ranges from 4.37 to 11.64%. All these indices meet the BS standard, American standard and Nepal standard, and are acceptable for road base and sub base courses of unbound pavement in roads.   doi: 10.3126/bdg.v12i0.2248 Bulletin of the Department of Geology, Vol. 12, 2009, pp. 29-42